Adaptive control and synchronization of the perturbed Chua's system - Thongchai Botmart (2018)
In this paper, we study perturbed Chua's system. First, we study the stability of equilibrium points of perturbed Chua's system. Then, we control the chaotic behavior of perturbed Chua's system to its equilibrium points using linear feedback control and adaptive control methods. Finally, we study chaos synchronization of perturbed Chua's system by using active control and adaptive control methods. © 2006 IMACS.